Hubungan Antara Pengetahuan Ibu tentang Kontrasepsi KB Suntik 1 bulan dengan Kepatuhan Jadwal Kunjungan Ulang di Polindes Bangkalan Madura - Nurlailatul Jannah; Fauziah Fitri Hernanto (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Family planning program is an effort to overcome population problems of population. Family planning is used to control birth in order to improve welfare of mother and child. Aim of this research is to know the correlation between knowledge of mother about one month injection contraceptive and obedience to schedule of revisit in Polindes Janteh Kwanyar Bangkalan Madura. This research constitutes analytical research. Population of all acceptors of one month injection contraceptives is 148 mothers. And the size of the sample is 65 mothers obtained by quota sampling. Data is collected by using a closed end questionnaire sheet. Then, data is processed with descriptive analysis consisting of editing, coding, scoring, and tabulating. Then, data is analyzed with Fisher exact test. Based on the results of the research, there are 65 mothers who participate in one month injection contraceptives and among them who have sufficient knowledge is 43 (66%) and who never revisit is 44 (68%). Result of the research indicates that there is no correlation between knowledge of a mother about one month injection contraceptive and obedience to schedule of revisit in Polindes Janteh Kwanyar Bangkalan Madura. From Fisher's exact test, ρ = 0.38, α = 0.05 where ρ > α so that H1 is rejected and H0 is accepted. It means there is no correlation between mother's knowledge about one month injection contraceptive and obedience to schedule of revisit. Conclusion of this research shows that there is another factor which causes mothers not complying to conduct revision, that is comprehension factor about instruction, quality of interaction factor, social factor and family and faith factor, attitude and personality factor. Therefore, it is highly important for us, as healthy professionals, to provide counseling about one month injection contraceptives.